Withania coagulans fruit extract antiulcerogenic effect: comparative study with lansoprazole and ranitidine in rats - Naheed Amir; Hassan Abu Damir; Karam Ghazal-Aswad; Mohamed Hassan; Mukhtar Adem; Mahmoud A. Ali; Salim Bastaki; Ernest Adeghate; Abdu Adem (Frontiers in Medicine)
BackgroundPeptic ulcer disease (PUD) arises from an imbalance between harmful factors like gastric acid and pepsin, and the protective mechanisms of the gastrointestinal lining, particularly the mucus–bicarbonate barrier. Standard treatments include proton pump inhibitors (e.g., lansoprazole) and histamine H₂-receptor antagonists (e.g., ranitidine), but these can have adverse effects. Withania coagulans, a plant used in Ayurvedic medicine, has traditionally been considered to have anti-ulcer properties. This study investigated the potential of W. coagulans fruit extract to protect against gastric ulcers, possibly via H₂ receptor antagonism.AimTo evaluate the gastroprotective effects and underlying mechanisms of W. coagulans fruit extract in a rat model of gastric ulcer.MethodsA dose–response study was conducted using rats divided into six groups: naïve, ulcer control, and four groups treated with W. coagulans extract (1, 5, 10, or 20 mg/kg). Acidified ethanol was used to induce ulcers. In another experiment, pylorus-ligated rats were used to assess the extract’s effect on gastric acid secretion in response to dimaprit, a histamine analog. For efficacy comparison, rats were pretreated with W. coagulans, lansoprazole, or ranitidine before ulcer induction. Gastric tissues were analyzed for biochemical markers, including cytokines, mucus, prostaglandin E2 (PGE2), and myeloperoxidase activity.ResultsThe 10 mg/kg dose was most effective in reducing gastric ulceration. The extract reduced gastric acid secretion, like H₂ blockers. It also showed stronger antioxidant activity in gastric tissues compared to lansoprazole and ranitidine. Additionally, it reduced pro-inflammatory cytokines (IL-1β, TNF-α, IL-6), increased anti-inflammatory cytokines (IL-10, TGF-β), enhanced mucus and PGE2 production, and lowered myeloperoxidase activity.ConclusionWithania coagulans fruit extract at 10 mg/kg significantly protects against acid-induced gastric ulcers. Its effects are comparable to H₂ receptor blockers and include notable antioxidant and anti-inflammatory benefits.